2021
DOI: 10.5090/jcs.21.039
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Cancer in Korea: Epidemiology and Treatment Patterns

Abstract: According to statistics from 2017, esophageal cancer is the fifteenth most common cancer and the eleventh most common cause of cancer-related death in Korea. The most common pathology is esophageal squamous cell carcinoma. Moreover, the incidence of esophageal cancer has been gradually decreasing in Korea, and the percentage of early-stage cases has gradually increased to the point that it is higher than that of other countries. The 5-year relative survival rate has improved over time. Approximately 800 esopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 8 publications
0
13
1
Order By: Relevance
“…Their findings that 92% recurrent were observed in less than 2 years after radical esophagectomy have a similar trend as our findings, which was much higher than the 30-40% by Chinese surveillance [ 1 ]. The difference between their and our findings might be due to the difference in the composition of pathological types (squamous cell: 83.4% in their study vs. 91.9% in our study), age (mean: 65.2 years old in their study vs. 58 years old in our study) [ 11 , 12 ] and living environment and habits [ 13 15 ]. They also found that patients with lymph node metastasis survived significantly longer than those metastasized to other organs and patients after surgical or additional postoperative chemotherapy lived longer than those who received other treatments.…”
Section: Discussioncontrasting
confidence: 82%
“…Their findings that 92% recurrent were observed in less than 2 years after radical esophagectomy have a similar trend as our findings, which was much higher than the 30-40% by Chinese surveillance [ 1 ]. The difference between their and our findings might be due to the difference in the composition of pathological types (squamous cell: 83.4% in their study vs. 91.9% in our study), age (mean: 65.2 years old in their study vs. 58 years old in our study) [ 11 , 12 ] and living environment and habits [ 13 15 ]. They also found that patients with lymph node metastasis survived significantly longer than those metastasized to other organs and patients after surgical or additional postoperative chemotherapy lived longer than those who received other treatments.…”
Section: Discussioncontrasting
confidence: 82%
“…Early detection and early treatment may in turn account for the relatively higher survival. Consistently, Japan and Korea with more extensive screening programs also had better survivals of EC (5‐year relative survival in Korea: 33.4%, and in Japan: 41.5%) 35,36 . Although bias in screening cannot be ruled out, paralleled significant declines in age‐standardized mortality rates for EC in screening areas were observed (Figure S1).…”
Section: Discussionmentioning
confidence: 55%
“…This pattern is likely to be related to longstanding population‐based endoscopic screening programs for early detection of EC in China, while the lack of screening may have led to more advanced stages at diagnosis in the United States 9 . Consistently, Japan and Korea with mass screening programs had significantly higher proportions of early stage ECs (Stage I: 30% in Korea; 32% in Japan) 35,36 . In addition, the stage‐specific survival in China was also better than that in the United States.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Esophageal cancer (EC) is the sixth leading cause of cancer-related mortality worldwide, accounting for 544,000 deaths in 2020 [ 1 , 2 ]. Despite advances in diagnostic and therapeutic modalities, the survival outcomes of patients with EC are not yet satisfactory.…”
Section: Introductionmentioning
confidence: 99%